Crowd Framework Untuk Pengembangan Film Animasi 3D - ., Sukoco (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
ABSTRACT: Crowd has been widely used in a variety of commercial products games and movies. The films were well-funded, has been widely used technique to give the crowd a colossal spectacular action picture. Although it has great potential but inIndonesiathe study of the crowd is still small. This paper aims to conduct a study on developing a framework for crowd simulation in the development of 3D animation.Keywords: Animation, FrameworkÂ ABSTRAK : Crowd telah banyak dipakai dalam berbagai produk komersial game dan film. Film-film yang berdana besar, telah banyak menggunakan teknik crowd Â untuk memberikan gambaran aksi kolosal yang spektakuler.Walaupun memiliki potensi yang besar tetapi di Indonesiastudi mengenai crowd masih sedikit. Paper ini bertujuan untuk melakukan studi mengenai framework untuk mengembangkan simulasi crowd Â dalam pengembangan animasi 3D.Katakunci : Animasi, Framework